The Time Value and Practice Path of the Integration of Sports Spirit into Ideological and Political Teaching in Colleges and Universities - Yun Luo (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The Chinese sports spirit serves a value-oriented purpose, and the cultural resources and typical cases of sports spirit are practical means for fostering the identification of socialist core values. The inclusion and coordination of ideological and political courses in universities should be carefully considered within the broader framework of "cultivating morality and cultivating people." This study aims to offer a comprehensive reference for the implementation of ideological and political education within the context of physical education. The article utilises SPSS 20.0 statistical software and an Excel worksheet to collect and organise survey questionnaire data obtained by our research institute. It performs quantitative analysis tasks, including data calculation and the creation of graphical representations. Additionally, research is conducted using methods such as questionnaires, surveys, and literature reviews. A sample of 300 students will be randomly selected from the University of Science and Technology. Questionnaires will be distributed to these students, and on-site filling and recycling methods will be employed. The study will focus on the current state of ideological and political education in college physical education. The combined percentage of male and female students who perceived the physical education class as reasonable was 22.87% of the total student population. However, a significant proportion of both male and female students believe that it is inappropriate to open this class. The empirical study on the proficiency of sports skills revealed that, following a mandatory nine-year education, students admitted to universities across all levels are capable of mastering 1-2 sports disciplines, constituting 68.48% of the overall population. We can establish a "unified library system," "ideological and political class competition," and other "walking classes" to form various teacher groups in the ideological and political class. These groups may include teachers in the ideological and political classes as well as Olympic champions.